Effects of satisfaction, subjective norms,and self-efficacy on job application intentions of student interns - Putra, Ibnu Handono; Purba, Debora Eflina (UI Scholars Hub, 2020)
Internship programs can serve as recruitment and selection strategies that facilitate data collection on the abilities of potential employees to manage their daily work duties. This study aims to examine factors that may influence a student intern’s intentions to apply to convert the internship into a permanent employee position at the same company after graduating from university. The study is grounded in the theory of planned behavior to probe whether internship satisfaction, subjective norms, and self-efficacy are predictors of the intentions of student interns to apply for jobs at companies that offer internship programs. Data collected from 261 Indonesian university students demonstrated that internship satisfaction and subjective norms positively and significantly predicted the intentions of student interns to apply to convert their internships into permanent jobs at the same company. However, self-efficacy did not predict such conversion intentions. Finally, the practical implications of these outcomes are discussed, and directions for prospective research are suggested.